2020
DOI: 10.1155/2020/5893642
|View full text |Cite
|
Sign up to set email alerts
|

The Induced Membrane Technique for the Management of Segmental Tibial Defect or Nonunion: A Systematic Review and Meta-Analysis

Abstract: Purpose. To identify the predicting factors for union and infection after applying the induced membrane technique (IMT) for segmental tibial defects. Methods. A systematic review was carried out following the PRISMA guidelines. All databases were searched for articles published between January 2000 and February 2018 using the keywords “Masquelet technique” and “induced membrane technique.” Studies in English reporting more than 5 cases with accessible individual patient data were included. A meta-analysis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 30 publications
0
36
0
1
Order By: Relevance
“…Implantation of large amounts of allograft, induced membrane technique or non-vascularized autogenous fibular graft for reconstruction of large tibial defects had been associated with greater risk of infection, graft rejection, fracture, nonunion, and fear of disease transmission, especially when associated with extensive scarring, and the fibular graft may not undergo hypertrophy [5] , [6] , [10] . It also did not solve the leg-length discrepancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Implantation of large amounts of allograft, induced membrane technique or non-vascularized autogenous fibular graft for reconstruction of large tibial defects had been associated with greater risk of infection, graft rejection, fracture, nonunion, and fear of disease transmission, especially when associated with extensive scarring, and the fibular graft may not undergo hypertrophy [5] , [6] , [10] . It also did not solve the leg-length discrepancy.…”
Section: Discussionmentioning
confidence: 99%
“…It provided a large graft of the ipsilateral fibula raised on a pedicle of the peroneal artery, aligned and fixed to the tibia; avoiding exposure of the site that is vulnerable to infection and facilitated wound healing without prolonged hospitalization. The Masquelet technique was relatively ineffective in achieving union in the reconstruction of great tibial defects and was associated with a high rate of infection [5] , [6] . However, the leg-length discrepancy and an acceptable limb alignment had not been solved by the abovementioned techniques [4] , [7] .…”
Section: Introduction and Importancementioning
confidence: 99%
“…14 Lengthy treatment time, pain during bone transport, disruption of the patient's daily activities is some of the disadvantages associated with the Ilizarov technique. 15 Tissue engineering has the potential to overcome all the abovelisted limitations of conventional techniques. More specifically, for the defects in bone alone (vascularized or non-vascularized), cartilage alone and in osteochondral regions.…”
Section: Introductionmentioning
confidence: 99%
“…An external fixation device helps in the transposition and is removed after the consolidation of the newly formed bone 14 . Lengthy treatment time, pain during bone transport, disruption of the patient's daily activities is some of the disadvantages associated with the Ilizarov technique 15 …”
Section: Introductionmentioning
confidence: 99%
“…Many studies have recommended the use of antibiotic-loaded PMMA cement during the first stage of Masquelet 14 16 . Additionally, a systematic review and a meta-analysis have also suggested that the antibiotic-loaded PMMA cement might prevent repeated surgeries for bone grafting 17 . Previous studies have proved that the inclusion of antibiotics in the PMMA spacer can alter the characteristics of the induced membrane 18 , and that antibiotics play an important role in the gene expression profile of induced membrane and the regeneration of infected defects 19 .…”
Section: Introductionmentioning
confidence: 99%